2019
DOI: 10.1177/0044118x19826423
|View full text |Cite
|
Sign up to set email alerts
|

What Youth With Special Needs in Juvenile Justice Say About Reentry: Listening to Their Voice

Abstract: The purpose of this study was to listen to what youth with special needs in juvenile justice (JJ) settings say they need to be successful during reentry. The three instruments used to gain an understanding of their perspectives on reentry and their perceptions of barriers include (a) intake interviews, (b) focus groups, and (c) semi-structured post-release interviews. Major themes shared are related to reentry programming, post-release transition activities, barriers to success, influences, and outcomes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…2,194 students were identified with special needs. One study identified learning disability as the only category for special needs (Ruch & Yoder, 2018), and two identified LD, emotional disabilities, and other disabilities as primary categories for special needs (Mathur et al, 2020, 2021). One study (Sinclair et al, 2020) did not specify the type of special needs and only described their participants as receiving Individual Education Program (IEP) services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,194 students were identified with special needs. One study identified learning disability as the only category for special needs (Ruch & Yoder, 2018), and two identified LD, emotional disabilities, and other disabilities as primary categories for special needs (Mathur et al, 2020, 2021). One study (Sinclair et al, 2020) did not specify the type of special needs and only described their participants as receiving Individual Education Program (IEP) services.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth study addressed the importance of listening to youth voice. Mathur et al (2020) conducted a qualitative study to develop a thorough understanding of the reentry needs of youth with disabilities across three different points in time—arrival to the facility, during incarceration, and postrelease. Intake interviews were conducted with 38 youth (35 males and three females).…”
Section: Resultsmentioning
confidence: 99%
“…The tertiary-level codes were specific practices found within the primary codes of employment, education/training, and independent living and will be discussed toward the end of the "Results" section as a way for youth and transition specialists voices to be shared about what they have done that connected youth with positive outcomes. Mathur et al (2019b) suggested "capturing the voice of youth is more challenging than objectively examining the reentry process because youth perspectives are connected to their experience with the reentry process" (p. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Practices must be identified that are feasible to implement and have some level of acceptability by those implementing them. Mathur et al (2019b) provided an outlet for youth with disabilities who were in the juvenile justice system to share their voice on what the reentry process was like for them. The authors iterated a need for more youth perspectives, suggesting that by taking into account their experience, implementation of practices is likely to produce more productive outcomes.…”
Section: Current Practicesmentioning
confidence: 99%
“…Youth-focused programming is a strength-based approach where youth actively participate as partners in the planning, delivery, and evaluation of reentry services. Their voices are incorporated in setting goals and developing personalized plans for employment, education, and other treatment options (Gonsoulin, Darwin, & Read, 2012; Mathur, Griller Clark, Hartzell, Lacroix, & McTier, 2019). They receive personalized support from their transition specialist (TS) in self-determination of their reentry goals and coordination of the continuum of care (Griller Clark, 2018).…”
mentioning
confidence: 99%